Capital Regulation and Tail Risk - Enrico Perotti; Lev Ratnovski; Razvan Vlahu (Tinbergen Institute, 2011)
The paper studies risk mitigation associated with capital regulation, in a context when banks may choose tail risk assets. We show that this undermines the traditional result that higher capital reduces excess risk-taking driven by limited liability. When capital raising is costly, poorly capitalized banks may limit risk to avoid breaching the minimal capital ratio. A bank with higher capital has lesschance of breaching the ratio, so may actually take more risk. As a result, banks which have access to tail risk projects may take greater risk when highly capitalized.The results are consistent with stylized facts about pre-crisis bank behavior, and suggest implications for the optimal design of capital regulation.
Keywords: E6; F3; F4; G2; G3; O16; 330; Bank Regulation; Risk Shifting; Capital Requirements; Tail Risk; Systemic Risk; Bankrisiko; Basler Akkord; Bankenliquidität; Bankenregulierung